Case control study of diffusion tensor imaging in Parkinson's disease - Chan, L‐L (BMJ Group, 2007)
BACKGROUND: Preliminary work has shown that diffusion tensor MRI (DTI) may contribute to the diagnosis of Parkinson's disease (PD). OBJECTIVES: We conducted a large, prospective, case control study to determine: (1) if fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values on DTI in the basal ganglia and substantia nigra are different between patients with PD and healthy controls; and (2) the predictive value of these parameters and their clinical utility. METHODS: DTI imaging was carried out in patients with PD and controls. FA and ADC values were obtained from various brain structures on the DTI scan using the diffusion tensor taskcard. The structures studied were: caudate, putamen, globus pallidus, thalamus and substantia nigra. RESULTS: 151 subjects (73 PD patients, 41 men, 32 women; mean age 63.6 years) and 78 age and sex matched control subjects were studied. The FA value of the substantia nigra in patients with PD was lower compared with controls (0.403 vs 0.415; p = 0.001). However, no significant differences were demonstrated for FA or ADC values of other structures. Multiple regression analysis revealed that the clinical severity of PD correlated inversely with the FA value in the substantia nigra in patients with PD (regression coefficient −0.019). No single FA value had both a high positive and negative predictive power for PD. CONCLUSIONS: We demonstrated in a large, prospective, case control study that the FA value in the substantia nigra on DTI was lower in PD compared with healthy controls, and correlated inversely with the clinical severity of PD. Further longitudinal studies would be helpful to assess the clinical utility of serial FA measurements of the substantia nigra in objective quantification of disease progression and monitoring of the therapeutic response.